MITOS BHATARI SRI DAN BUDAYA SUBAK BALI DALAM WUJUD ARSITEKTUR - Elren Joni; Alvin Hadiwono (Jurusan Arsitektur dan Perencanaan, 2023)
In Balinese culture, Subak and Bhatari Sri are two important symbols that are often used in traditional ceremonies. Subak is a traditional irrigation system that has been used for centuries to irrigate rice fields and gardens in rural areas. Meanwhile, Bhatari Sri is a goddess who is considered the patroness of agriculture and abundance. Jatiluwih, a region in Bali, is famous for its beautiful and fertile rice fields, which have been recognized as a World Heritage Site by UNESCO. The symbolism of Subak and Bhatari Sri attracts tourists to this area as it reflects the rich cultural values that are important in the daily lives of Balinese people. When tourists visit Jatiluwih, they can learn about the Subak irrigation system and how the Balinese community maintains its sustainability. They can also witness traditional ceremonies involving Bhatari Sri, such as the Ngembak Geni ceremony held annually to celebrate the abundance of the harvest. By promoting the symbolism of Subak and Bhatari Sri as a tourist attraction, Jatiluwih can attract tourists who want to learn about Balinese culture and experience its lush natural beauty. It can also assist the local community in preserving its cultural heritage and earning income from a sustainable tourism industry. The purpose of this research is to understand the concept and also know the myth of Bhatari Sri and Balinese Subak culture in the form of architecture. The research method used is descriptive qualitative with observation data collection techniques and documentation studies. The results of this research are that the Balinese people uphold the traditions inherited from their ancestors and also take good care of nature which is adjusted to the concept of tri hita in architectural buildings in the Balinese region. Keywords: balinese culture; goddess bhatari sri; subak irrigation system; sustainable tourism industry jatiluwih rice fields Abstrak Dalam budaya Bali, Subak dan Bhatari Sri adalah dua simbol penting yang sering digunakan dalam upacara tradisional. Subak adalah sistem irigasi tradisional yang telah digunakan selama berabad-abad untuk mengairi sawah dan kebun di daerah pedesaan. Sementara itu, Bhatari Sri adalah dewi yang dianggap sebagai pelindung pertanian dan kelimpahan. Jatiluwih, sebuah wilayah di Bali, terkenal dengan sawahnya yang indah dan subur, yang telah diakui sebagai Situs Warisan Dunia oleh UNESCO. Simbolisme Subak dan Bhatari Sri menarik wisatawan ke daerah ini karena mencerminkan nilai-nilai budaya yang kaya yang penting dalam kehidupan sehari-hari orang Bali. Ketika wisatawan mengunjungi Jatiluwih, mereka dapat belajar tentang sistem irigasi Subak dan bagaimana komunitas Bali mempertahankan keberlanjutannya. Mereka juga dapat menyaksikan upacara adat yang melibatkan Bhatari Sri, seperti upacara Ngembak Geni yang diadakan setiap tahun untuk merayakan kelimpahan panen. Dengan mempromosikan simbolisme Subak dan Bhatari Sri sebagai objek wisata, Jatiluwih dapat menarik wisatawan yang ingin belajar tentang budaya Bali dan mengalami keindahan alamnya yang subur. Ini juga dapat membantu komunitas lokal dalam melestarikan warisan budayanya dan memperoleh pendapatan dari industri pariwisata yang berkelanjutan. Adapun tujuan dari penelitian ini yaitu untuk memahami konsep dan juga mengetahui mitos Bhatari Sri dan budaya Subak Bali dalam wujud arsitektur. Metode penelitian yang digunakan yaitu deskriptif kualitatif dengan teknik pengumpulan data observasi dan studi dokumentasi. Adapun hasil dari penelitian ini yaitu masyarakat Bali memegang teguh tradisi warisan dari leluhur mereka dan juga menjaga alam dengan baik yang disesuaikan dengan konsep tri hita dalam bangunan arsitektur di wilayah Bali.